Granular temporary plugging agent and preparation method thereof
By using low-density particle temporal agents in low-permeability oil and gas reservoirs, the problems of high density, poor sealing performance and poor degradation performance in the prior art are solved, and efficient reservoir transformation and oil and gas development are achieved.
Patent Information
- Application Number
- CN202411650339.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-19
AI Technical Summary
In the prior art, temporary plugging agents have problems such as high density, poor sealing performance and poor degradation performance in the development of low-permeability oil and gas reservoirs, making it difficult to achieve efficient reservoir transformation.
A low-density particle temporary plugging agent is adopted, and its components include acrylamide, comonomer, crosslinking agent, polyvinyl alcohol, modified nanoblending materials, etc., and an interpenetrating network structure is formed through a specific preparation method to achieve low density, high sealing performance and excellent degradation performance.
It has achieved a low density, good sealing performance and excellent degradation performance in the slot temporary agent system, which is suitable for efficient development of low-permeability oil and gas reservoirs.
Smart Images

Figure CN119144306B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field exploitation, and in particular to a particle temporary plugging agent and a preparation method thereof. Background Art
[0002] At present, temporary plugging and diversion fracturing technology is widely used on site to increase production capacity. This technology uses the temporary plugging effect of temporary plugging agents to promote the opening and extension of secondary fractures, thereby greatly increasing the complexity of fractures, thereby obtaining a larger reservoir transformation volume, thereby increasing the production of a single well. Obviously, the core of this technology is to form new fractures, and the selection of appropriate temporary plugging agents is a crucial link in the process of forming new fractures.
[0003] There are many temporary plugging agents in the prior art, such as solid temporary plugging agents, fiber, particle-type cross-linking, liquid gel-type cross-linking, velvet capsules and other temporary plugging materials. Solid temporary plugging agents are subject to certain restrictions in actual use on site due to special requirements on solubility; fiber-type temporary plugging materials have limited pressure bearing capacity and poor mechanical properties, and are not suitable for plugging cracks with large openings; the plugging layer formed by the bridge of rigid particle-type temporary plugging materials has poor integrity and is difficult to recover after instability. It requires a combination of multiple particle sizes to effectively increase the particle packing density, which is difficult to construct and generally difficult to achieve a relatively ideal plugging effect in the fracturing crack; liquid rubber plug-type cross-linked temporary plugging materials have low strength, poor pressure bearing capacity, and difficult to control the gel breaking process; velvet capsule temporary plugging materials have the disadvantages of a narrow range of applicable temperature and pressure conditions and a small range of applicable pore crack sizes.
[0004] Granular cross-linked temporary plugging materials have good injectability and use their deformation ability to plug cracks with high strength. Their expansion and surface adhesion make it easier to form effective plugging in cracks. They can also self-degrade into low-viscosity aqueous solutions under the influence of formation temperature, which has significant advantages when used in unconventional reservoir fracturing transformation. However, they also have poor mechanical properties and are easily damaged by shear, and the degradation rate and degradation rate are difficult to guarantee. It is most effective to use clear water or low-viscosity slippery water as the temporary plugging agent carrier liquid segment plug. If a high-viscosity carrier liquid is used, not only will the temporary plugging particles be too dispersed and difficult to aggregate and bridge, but the high net pressure will further increase the crack width and reduce the plugging efficiency. High-density temporary plugging materials are difficult to achieve remote transportation and balanced laying to plug and create cracks in high-stress fracturing cracks in unconventional reservoirs.
[0005] In view of the above problems, in order to improve the safe and efficient development of low-permeability oil and gas reservoirs, there is an urgent need for a temporary plugging agent system in fractures with low density, good plugging performance and excellent degradation performance.
[0006] The above contents are only used to assist in understanding the technical solution of the present invention and do not constitute an admission that the above contents are prior art. Summary of the invention
[0007] The main purpose of the present invention is to provide a particle temporary plugging agent and a preparation method thereof, aiming to solve or partially solve the above-mentioned problems.
[0008] To achieve the above object, the present invention provides a particle temporary plugging agent, the density of the particle temporary plugging agent is lower than the density of water, and the particle temporary plugging agent includes the following components in terms of mass percentage:
[0009] Acrylamide: 17-23%;
[0010] Comonomer: 1-2%;
[0011] First cross-linking agent: 0.2-0.27%;
[0012] Polyvinyl alcohol: 5-10%;
[0013] Second cross-linking agent: 1-2%;
[0014] Initiator: 0.06-0.12%;
[0015] Initiator: 0.01-0.02%;
[0016] Modified nano-blended materials: 3-6%;
[0017] Dispersant: 0.3-0.6%;
[0018] The rest is distilled water;
[0019] Wherein, the first cross-linking agent is one or more of ethylene glycol dimethacrylate, polyethylene glycol diacrylate, and trimethylolpropane trimethacrylate;
[0020] The second cross-linking agent is one or both of β-cyclodextrin-boron complex and glycerol-boron complex;
[0021] The modified nano-blended material is a soda lime silicate modified by surface activation-silane coupling, in the form of hollow microspheres filled with air or CO2, with a true density of 0.6 g / cc and a compressive strength of 124 MPa.
[0022] Preferably, in the particle temporary plugging agent, the comonomer is one or more of 2-acrylamide-2-methylpropanesulfonic acid, p-styrenesulfonic acid, and trimethylolpropane trimethacrylate.
[0023] Preferably, in the granular temporary plugging agent, the initiator is two of ammonium persulfate, potassium persulfate and sodium bisulfite, and the mass ratio thereof is 1:1.
[0024] Preferably, in the particle temporary plugging agent, the initiator aid is N,N,N',N'-tetramethylethylenediamine.
[0025] Preferably, in the particle temporary plugging agent, the dispersant is one or more of sodium citrate, sodium metasilicate, and sodium pyrophosphate.
[0026] In order to achieve the above object, the present invention also provides a method for preparing the above-mentioned particle temporary plugging agent, comprising the following steps:
[0027] Add polyvinyl alcohol to distilled water, heat at a first temperature and stir until completely dissolved;
[0028] After the polyvinyl alcohol is completely dissolved to obtain a first solution, the first solution is cooled to room temperature;
[0029] Add distilled water to acrylamide and the comonomer, and stir thoroughly until they are completely dissolved to obtain a second solution;
[0030] The first solution is added to the second solution, and the mixture is stirred evenly. During the stirring, a dispersant is added, and after stirring until dissolved, the modified nano-blended material is added, and the mixture is stirred evenly to obtain a first mixture.
[0031] Adding a first crosslinking agent and an initiator to the first mixture and stirring evenly to obtain a second mixture;
[0032] Add the second cross-linking agent and the initiator to the second mixture, stir evenly, cover with a plastic wrap, and place in an oven to keep warm at the second temperature for reaction;
[0033] After the heat preservation reaction is completed, the finished product is taken out to obtain a polymerized jelly colloid, which is dried and crushed to obtain the particle temporary plugging agent.
[0034] Preferably, in the method for preparing the temporary plugging agent of particles, before the step of adding a second crosslinking agent and an initiating auxiliary agent to the second mixture, stirring evenly, covering with a plastic wrap, and placing in an oven for heat preservation reaction at a second temperature, the method further includes preparing a second crosslinking agent, and the method for preparing the second crosslinking agent includes:
[0035] adding β-cyclodextrin to deionized water to obtain a third solution;
[0036] Adding sodium tetraborate to the third solution, and adding sodium hydroxide to adjust the pH value of the solution to between 7 and 8, and continuously stirring at a third temperature until crystals gradually precipitate, wherein the third temperature is 40-80° C.;
[0037] The precipitated precipitate is collected by filtration, washed, and dried to obtain a β-cyclodextrin-boron complex.
[0038] Preferably, in the preparation method of the temporary plugging agent, before the step of adding the first solution to the second solution, stirring evenly, adding a dispersant during stirring, stirring until dissolved, adding a modified nano-blended material, stirring evenly, and obtaining the first mixture, the preparation method includes preparing a modified nano-blended material, and the step of preparing the modified nano-blended material includes:
[0039] Place the nano inorganic material in a 2% sodium hydroxide solution and stir evenly;
[0040] After the reaction is completed, washing and removing the unreacted nano-inorganic material to complete the surface activation of the nano-inorganic material;
[0041] The activated nano-inorganic material, silane coupling agent, γ-aminopropyltriethoxysilane and ethanol were placed in a three-necked flask, and ammonia water was added and magnetically stirred evenly. Then the temperature was raised to 45°C and stirring was continued for 2 hours. After the stirring was completed, the unreacted raw materials were washed to remove and the modified nano-blend material was obtained by drying.
[0042] Preferably, in the method for preparing the temporary plugging agent of particles, the first temperature is 90°C-95°C.
[0043] Preferably, in the method for preparing the temporary plugging agent of particles, the second temperature is 60°C-65°C.
[0044] The present invention has at least the following beneficial effects:
[0045] The particle temporary plugging agent provided by the present invention comprises the following components in terms of mass percentage: acrylamide: 17-23%; comonomer: 1-2%; first crosslinking agent: 0.2-0.27%; polyvinyl alcohol: 5-10%; second crosslinking agent: 1-2%; initiator: 0.06-0.12%; initiator aid: 0.01-0.02%; modified nano-blended material: 3-6%; dispersant: 0.3-0.6%; the rest is distilled water; wherein the first crosslinking agent is ethylene glycol dimethacrylate The modified nano-blended material is a soda lime silicate modified by surface activation-silane coupling, and is in the form of hollow microspheres filled with air or CO2, with a true density of 0.6 g / cc and a compressive strength of 124 MPa. The temporary plugging agent body in the seam thus obtained has low density, good plugging performance and excellent degradation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 A schematic diagram of a method for preparing a temporary plugging agent of particles provided by the present invention;
[0047] Figure 2 A schematic diagram of preparing a second cross-linking agent according to the present invention;
[0048] Figure 3 A schematic diagram of preparing a modified nano-blended material according to the present invention;
[0049] Figure 4 Schematic diagram of the interpenetrating network structure;
[0050] Figure 5 The graphs are the test results of the temporary plugging agent gel state mechanical properties of the embodiment and the comparative example;
[0051] Figure 6 The graphs are the experimental results of the state-to-state mechanical properties of temporary plugging agent particles of the embodiment and the comparative example;
[0052] Figure 7 is the self-degradation time of temporary plugging agent particles at different temperatures.
[0053] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0054] In the embodiments of the present invention, the term "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0055] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence.
[0056] In the embodiments of the present invention, the term "plurality" refers to two or more than two, and other quantifiers are similar.
[0057] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings. However, it can be understood by those skilled in the art that in the embodiments of the present invention, many technical details are proposed in order to enable the reader to better understand the present invention. However, even without these technical details and various changes and modifications based on the following embodiments, the technical scheme claimed in the present invention can also be implemented. The division of the following embodiments is for the convenience of description and should not constitute any limitation on the specific implementation of the present invention. The various embodiments can be combined and referenced with each other under the premise of no contradiction.
[0058] Current research has achieved good results in the development of low-density, high-strength gel systems. However, current technical methods still have shortcomings. In terms of improving system strength, the conventional method of adding inorganic materials to improve system performance will make the system density too high, and it is easy to deposit at the seam position and the bottom of the crack. In terms of reducing system density, for example, the method of introducing aeration agents to reduce the density of the gel system will inevitably sacrifice the strength of a part of the material, and it is very easy to fail when used in unconventional reservoir fracturing transformation; the method of using density regulators, on the one hand, the degree of integration of inorganic particles or low-density fibers with polymer matrix materials is not enough, and the gel particles expand and precipitate easily under high temperature conditions, causing filling failure. On the other hand, lightweight inorganic particles or low-density fibers are not easy to disperse during the preparation process, which greatly increases the difficulty of industrial production.
[0059] The invention provides a particle temporary plugging agent, which has a density lower than that of water and comprises the following components in terms of mass percentage: acrylamide: 17-23%; comonomer: 1-2%; first cross-linking agent: 0.2-0.27%; polyvinyl alcohol: 5-10%; second cross-linking agent: 1-2%; initiator: 0.06-0.12%; initiator aid: 0.01-0.02%; modified nano-blended material: 3-6%; dispersant: 0.3-0.6%; and the rest is distilled water.
[0060] Wherein, the first cross-linking agent is one or more of ethylene glycol dimethacrylate, polyethylene glycol diacrylate, and trimethylolpropane trimethacrylate.
[0061] The second cross-linking agent is one or both of β-cyclodextrin-boron complex and glycerol-boron complex.
[0062] Preferably, the mass percentage of acrylamide may also be 18%, 19%, or 21%.
[0063] Preferably, the mass percentage of the first cross-linking agent may also be 0.21%, 0.23%, or 0.25%.
[0064] Preferably, the mass percentage of polyvinyl alcohol may also be 6%, 7%, or 8%.
[0065] Preferably, the mass percentage of the initiator may also be 0.07%, 0.08%, or 0.1%.
[0066] Preferably, the mass percentage of the modified nano-blended material can also be 4% or 5%.
[0067] Preferably, the mass percentage of the dispersant may also be 0.4% or 0.5%.
[0068] The modified nano-blended material is a soda lime silicate modified by surface activation-silane coupling, in the form of hollow microspheres filled with air or CO2, with a true density of 0.6 g / cc and a compressive strength of 124 MPa.
[0069] The comonomer is one or more of 2-acrylamide-2-methylpropanesulfonic acid, p-styrenesulfonic acid, and trimethylolpropane trimethacrylate.
[0070] The initiators are two of ammonium persulfate, potassium persulfate and sodium bisulfite, and the mass ratio thereof is 1:1.
[0071] The initiator aid is N,N,N',N'-tetramethylethylenediamine.
[0072] The dispersant is one or more of sodium citrate, sodium metasilicate and sodium pyrophosphate.
[0073] Figure 1 The schematic diagram of the preparation method of the particle temporary plugging agent provided by the present invention is shown as follows: Figure 1 As shown. In step S100, polyvinyl alcohol is added to distilled water, heated at a first temperature and stirred until completely dissolved. The first temperature is 90°C-95°C. Preferably, the first temperature is 90°C. Specifically, polyvinyl alcohol can be added to a flask of distilled water, placed in a water bath, heated at the first temperature and stirred until completely dissolved.
[0074] In step S200, the polyvinyl alcohol is completely dissolved to obtain a first solution, which is then cooled to room temperature.
[0075] In step S300, distilled water is added to acrylamide and the comonomer, and the mixture is stirred until completely dissolved to obtain a second solution. Specifically, taking p-styrene sulfonic acid as the comonomer, acrylamide and p-styrene sulfonic acid are added to a flask containing distilled water, and the mixture is stirred until completely dissolved to obtain a second solution.
[0076] In step S400, the first solution is added to the second solution and stirred evenly. During stirring, a dispersant is added and stirred until dissolved, and then the modified nano-blended material is added and stirred evenly to obtain a first mixture.
[0077] In step S500, a first cross-linking agent and an initiator are added to the first mixture, and the mixture is stirred evenly to obtain a second mixture.
[0078] In step S600, the second crosslinking agent and the initiating auxiliary agent are added to the second mixture, stirred evenly, covered with a preservative film, and placed in an oven for heat preservation and reaction at a second temperature of 60°C-65°C.
[0079] After the heat preservation reaction is completed in step S700, the finished product is taken out to obtain a polymerized jelly colloid, which is dried and crushed to obtain the particle temporary plugging agent.
[0080] Example 1
[0081] The granular temporary plugging agent includes the following components in percentage by mass: acrylamide: 23%; comonomer (p-styrene sulfonic acid): 2%; first cross-linking agent (polyethylene glycol diacrylate): 0.27%; polyvinyl alcohol: 5%; second cross-linking agent (β-cyclodextrin-boron complex): 2%; initiator (potassium persulfate): 0.06%; initiator aid (N,N,N',N'-tetramethylethylenediamine): 0.01%; modified nano-blend material: 5%; dispersant (sodium pyrophosphate): 0.5%; the rest is distilled water.
[0082] The preparation method is as follows:
[0083] S1, weigh 5.0g of polyvinyl alcohol, add it into a flask containing 40.0g of distilled water, heat it in a water bath at 90℃ and stir it thoroughly until it is completely dissolved.
[0084] S2, cooling the completely dissolved polyvinyl alcohol to room temperature to obtain a first solution.
[0085] S3, weigh 23 g of acrylamide and 2 g of p-styrene sulfonic acid, add them into a flask containing 22.67 g of distilled water, and stir them thoroughly until they are completely dissolved to obtain a second solution.
[0086] S4, then pour the dissolved polyvinyl alcohol solution (first solution) into the acrylamide solution (second solution) and stir evenly; under slow stirring conditions, add 0.5g of sodium pyrophosphate, stir until dissolved, then slowly add 5g of the modified nano-blended material, and stir for 2h until uniform;
[0087] S5, add 0.27 g of polyethylene glycol diacrylate and 0.06 g of potassium persulfate, and stir evenly;
[0088] S6, add 2g of β-cyclodextrin-boron complex and 0.01g of N,N,N',N'-tetramethylethylenediamine, stir evenly, cover with plastic wrap, put in an oven at 60°C, and keep warm for 8 hours;
[0089] S7, after the heat preservation reaction is finished, the finished product is taken out to obtain the polymer jelly; further prepared into inorganic composite-interpenetrating network polymer plugging agent particles, the jelly is cut into uniform small pieces; the treated dispersion jelly small pieces are placed in a vacuum constant temperature drying oven at 80°C for drying for 12 hours; the dried jelly is placed in a grinder and crushed; the crushed particles are further sieved using a standard sieve to obtain inorganic composite-interpenetrating network polymer plugging agent particles with relatively uniform particle size, namely, a granular temporary plugging agent.
[0090] It should be noted that the interpenetrating polymer network is a type of chemically blended network composite system composed of two or more polymer networks that penetrate or entangle each other, in which one network is formed by on-site polymerization or cross-linking in the direct presence of another network, and the networks are physically penetrated, and the strength and temperature resistance of the formed system are greatly improved. Figure 4 As shown, (a) represents the first network polymerization, (b) represents the second network polymerization, and (c) is an interpenetrating polymer network. The present invention polymerizes the first network into acrylamide and the second network into polyvinyl alcohol, and then uses the crosslinking agent provided by the present invention to polymerize the two networks together to form an interpenetrating polymer network structure.
[0091] Example 2
[0092] The granular temporary plugging agent includes the following components in percentage by mass: acrylamide: 19%; comonomer (p-styrene sulfonic acid): 2%; first cross-linking agent (polyethylene glycol diacrylate): 0.27%; polyvinyl alcohol: 5%; second cross-linking agent (β-cyclodextrin-boron complex): 2%; initiator (potassium persulfate): 0.06%; initiator aid (N,N,N',N'-tetramethylethylenediamine): 0.01%; modified nano-blend material: 6%; dispersant (sodium pyrophosphate): 0.5%; the rest is distilled water.
[0093] Example 3
[0094] The granular temporary plugging agent includes the following components in percentage by mass: acrylamide: 19%; comonomer (p-styrene sulfonic acid): 2%; first cross-linking agent (polyethylene glycol diacrylate): 0.23%; polyvinyl alcohol: 6%; second cross-linking agent (β-cyclodextrin-boron complex): 2%; initiator (potassium persulfate): 0.07%; initiator aid (N,N,N',N'-tetramethylethylenediamine): 0.01%; modified nano-blend material: 4%; dispersant (sodium pyrophosphate): 0.5%; the rest is distilled water.
[0095] Example 4
[0096] The granular temporary plugging agent includes the following components in percentage by mass: acrylamide: 19%; comonomer (p-styrene sulfonic acid): 2%; first cross-linking agent (polyethylene glycol diacrylate): 0.23%; polyvinyl alcohol: 7%; second cross-linking agent (β-cyclodextrin-boron complex): 2%; initiator (potassium persulfate): 0.08%; initiator aid (N,N,N',N'-tetramethylethylenediamine): 0.01%; modified nano-blend material: 5%; dispersant (sodium pyrophosphate): 0.5%; the rest is distilled water.
[0097] Example 5
[0098] The granular temporary plugging agent includes the following components in percentage by mass: acrylamide: 19%; comonomer (p-styrene sulfonic acid): 2%; first cross-linking agent (polyethylene glycol diacrylate): 0.23%; polyvinyl alcohol: 8%; second cross-linking agent (β-cyclodextrin-boron complex): 2%; initiator (potassium persulfate): 0.1%; initiator aid (N,N,N',N'-tetramethylethylenediamine): 0.01%; modified nano-blend material: 6%; dispersant (sodium pyrophosphate): 0.5%; the rest is distilled water.
[0099] The method further includes step S800 of preparing a second cross-linking agent. Figure 2 The schematic diagram of preparing the second cross-linking agent of the present invention is shown. Figure 2 shown.
[0100] In step S810, β-cyclodextrin is added to deionized water to obtain a third solution.
[0101] In step S820, sodium tetraborate is added to the third solution, and sodium hydroxide is added to adjust the pH value of the solution to between 7 and 8, and stirring is continued at a third temperature until crystals gradually precipitate, wherein the third temperature is 40-80° C.;
[0102] In step S830, the precipitated precipitate is collected by filtration, washed, and dried to obtain a β-cyclodextrin-boron complex.
[0103] It should be noted that the preparation method of polyvinyl alcohol adopts a complex body sustained-release system as a polymerization monomer di-crosslinking agent. Specifically, the formula of polyvinyl alcohol includes a main body and a boron ion precursor guest, wherein the main body includes β-cyclodextrin with a weight ratio of 5%-12.5%, and the boron ion precursor guest includes sodium tetraborate with a weight ratio of 3.5-9%, and the mass ratio of the main body to the boron ion precursor guest is 1:4.
[0104] In the prior art, polyvinyl alcohol (PVA) crosslinking agents are often borax or boric acid. Previous studies have shown that both of these crosslinking agents have the problem of too fast release of boron ions after dissolution, resulting in local over-crosslinking of the polymerized monomers and failure to form a uniform interpenetrating network. In view of the above problem, the present invention proposes a method of using a complex body sustained-release system as a crosslinking agent for the polymerized monomers, thereby solving the problem.
[0105] Example 6
[0106] (1) Add 5.6 g of β-cyclodextrin and 40.4 ml of deionized water to a three-necked flask to prepare a solution, and slowly add 4 g of sodium tetraborate to the cyclodextrin solution; (2) Add a regulator, sodium hydroxide (NaOH), to adjust the pH value of the solution to between 7 and 8, and continue to stir the mixture for 3 hours under mild heating conditions (40-80°C) to promote the formation of the complex; (3) Then let the mixture cool naturally to room temperature, and the complex will gradually crystallize and precipitate; (4) Collect the precipitate by filtration, and then wash the precipitate with ethanol or acetone to remove unreacted raw materials; (5) Dry the product in a vacuum oven to constant weight to obtain a β-cyclodextrin-boron complex.
[0107] Wherein, step S900 is also included before step S400. Figure 3 The schematic diagram of preparing modified nanocomposite materials is shown. Figure 3 shown.
[0108] In step S910, the nano inorganic material is placed in a 2% sodium hydroxide solution and stirred evenly;
[0109] After the reaction is completed in step S920, the unreacted nano-inorganic material is washed away to complete the surface activation of the nano-inorganic material;
[0110] In step S930, the activated nano-inorganic material, silane coupling agent, γ-aminopropyltriethoxysilane, and ethanol are placed in a three-necked flask, and ammonia water is added and magnetically stirred evenly, then the temperature is raised to 45° C. and stirring is continued until the reaction is complete. After the reaction is completed, the unreacted raw materials are washed to remove and the modified nano-blended material is dried.
[0111] Example 7
[0112] ① Surface activation: Place 10g of nano-inorganic material in 200ml of 2% sodium hydroxide solution, stir at a constant speed for 3h at 70℃, wash with ethanol or acetone to remove unreacted raw materials, and dry in an oven at 60℃ for 24h;
[0113] ② Modification: Place 10g of activated nano-inorganic material, 10ml of silane coupling agent: γ-aminopropyltriethoxysilane, and 200ml of ethanol in a three-necked flask, add 20ml of ammonia water and stir magnetically for 1h, then heat to 45℃ and continue stirring for 2h. After that, wash with ethanol or acetone to remove unreacted raw materials, and dry in a 60℃ oven for 24h.
[0114] ③ Disperse and suspend before specific preparation: Before adding the surfactant-modified nano-inorganic material into the temporary plugging agent system, a certain concentration of mass (equivalent to 10% of the concentration of low-density inorganic material) (equivalent to 10% of the concentration of low-density inorganic material) of dispersant: sodium pyrophosphate (Na4P2O7) is added to the temporary plugging agent solution in the preparation process. The negative charge provided by the dispersant after dissociation in water can be adsorbed on the surface of the particles to form electrostatic repulsion, thereby preventing aggregation between particles, effectively dispersing solid particles, and avoiding sedimentation and agglomeration. At the same time, the polyvinyl alcohol in the temporary plugging agent solution has the characteristics of a non-ionic surfactant. On the one hand, it reduces the surface tension of the solution and makes the particles easier to disperse. On the other hand, after being adsorbed on the surface of the particles, it can produce a steric hindrance effect to prevent the approach between particles, thereby reducing aggregation. At the same time, the temporary plugging agent solution has a certain viscosity, which increases the suspension stability of the particles.
[0115] In order to further verify the effect of the low-density granular temporary plugging agent provided by the present invention, particle dispersion observation, density test, gel-state reservoir modulus test, plugging performance test and degradation rate test were carried out during the preparation process of the low-density granular temporary plugging agent provided by the present invention.
[0116] Comparative Example 2
[0117] Conventional PAM-based interpenetrating network hydrogel temporary plugging agent for oil fields.
[0118] Comparative Example 3
[0119] Nanocomposite PAM / MMT hydrogel temporary plugging agent.
[0120] Comparative Example 4
[0121] Expandable granular type temporary plugging agent for fractures used in block x of xx oilfield.
[0122] The following will provide a comparative description of Example 1 and Comparative Examples 1 to 4 to demonstrate the beneficial effects of the present invention.
[0123] (1) Dispersion test
[0124] The premise of reducing the density of the system by adding low-density nano-inorganic materials is that the inorganic materials can be effectively dispersed in the system. In order to explore the improvement of the dispersibility of the low-density nano-inorganic material treatment process involved in the present invention, a nano-inorganic material dispersibility test was carried out. At a certain rotation speed, a certain concentration (dispersant sodium pyrophosphate) and a certain concentration (3-7wt%) of nano-inorganic material were slowly added to the pre-mixed liquid of the system involved in the present invention, and the mixture was placed at the reaction temperature to stand and observe the dispersion of the materials.
[0125] It should be noted that the pre-mixed liquid is the mixed liquid obtained by adding the first solution to the second solution in step S400. Dispersant and modified nano-blended material have not yet been added to the pre-mixed liquid.
[0126] Dispersants were added to the premixed liquids numbered 6 to 9 in Table 1. The experimental results are shown in Table 1. The experimental results show that: since the selected low-density inorganic materials are nano-sized particles with a relatively high surface area to volume ratio, the van der Waals force between the particles promotes the aggregation of the particles. At the same time, the material density is low and it is not easy to disperse in the solution, which increases the difficulty of preparing the temporary plugging agent system. Polyvinyl alcohol monomers exist in the premixed liquid. Polyvinyl alcohol itself has surfactant properties, but they are not strong and the dispersion effect is not good. By adding dispersants, the surface tension of the solution can be further reduced, the dispersion ability can be improved, and the dispersion effect can be significantly improved. On the one hand, the surface tension of the solution can be reduced during the preparation process, making the particles easier to disperse. On the other hand, after being adsorbed on the surface of the particles, a steric hindrance effect can be generated to prevent the approach between particles, thereby reducing aggregation.
[0127] Table 1 Test results of nano-inorganic material dispersion
[0128]
[0129] (2) Density test
[0130] The temporary plugging agent involved in the present invention is a low-density temporary plugging agent, which reduces the density of the temporary plugging agent system by adding low-density nano inorganic materials, and focuses on the density of the prepared temporary plugging agent.
[0131] In order to reflect the performance of the temporary plugging agent system involved in the present invention, this example is compared and explained by the examples and comparative examples. Example 1 is the particle temporary plugging agent provided by the present invention, comparative example 1 is a conventional PAM-based hydrogel temporary plugging agent in oil fields, comparative example 2 is a conventional PAM-based interpenetrating network hydrogel temporary plugging agent in oil fields, comparative example 3 is a nanocomposite PAM / MMT hydrogel temporary plugging agent, and comparative example 4 is an expanded particle-type fracture temporary plugging agent used in the x block of the xx oil field. Since the temporary plugging agent particles prepared by the present invention have water absorption, the particle density is measured by the ethanol displacement method.
[0132] The specific steps are as follows: Use a balance to accurately measure the mass of a certain amount of gel before drying and the mass of the particle sample after drying (recorded as m1); Pour an appropriate amount of ethanol into a clean, dry measuring cylinder and record the initial volume of ethanol (recorded as V0); Gently place the gel and particle samples into the ethanol in the measuring cylinder with tweezers to avoid stirring up too many bubbles. Wait for the ethanol surface to calm down and ensure that the particles are completely immersed, but no ethanol overflows; When the ethanol surface is stable, record the total volume of ethanol and particles (recorded as V1). The volume displaced by the particles in ethanol is equal to the difference between the final volume and the initial volume (V1-V0=ΔV); The density (ρ) of the particles can be calculated by dividing their mass by their volume, that is, ρ=m1 / ΔV.
[0133] The experimental results are shown in Table 2, and the experimental results show that the addition of the inorganic nanomaterials involved in the present invention can effectively adjust the density of the gel system. Due to its inert filling effect, when the low-density nanoparticles are evenly dispersed in the gel matrix, they can occupy a certain volume but contribute less mass, thereby effectively reducing the overall density, that is, the low-density characteristics of the nanoparticles themselves are passed to the entire composite material. At the same time, the addition of nanoparticles can modify the structure of the gel system. On the one hand, by forming gaps in the gel network or reducing the close stacking between polymer chains, on the other hand, it can be used as a physical or chemical partition to prevent the close cross-linking of polymer chains, thereby forming more microporous structures in the gel and reducing the system density.
[0134] Table 2 Density test results of temporary plugging agent system
[0135]
[0136] (3) Mechanical properties test
[0137] The temporary plugging agent system in the fractures involved in the present invention is actually cross-linked and dried hydrogel particles on the ground, which are hydrogels that reach swelling equilibrium when they take effect in the fracturing fractures. This example tests the mechanical properties of the system, and compares and illustrates them through the embodiments and comparative examples. The experimental methods are divided into gel-state mechanical properties and particle-state mechanical properties. Example 1 is a particle temporary plugging agent provided by the present invention, comparative example 1 is a conventional PAM-based hydrogel temporary plugging agent for oil fields, comparative example 2 is a conventional PAM-based interpenetrating network hydrogel temporary plugging agent for oil fields, and comparative example 3 is a nanocomposite PAM / MMT hydrogel temporary plugging agent.
[0138] 1) Gel mechanical properties
[0139] When testing the compressive strength of the temporary plugging agent in gel state, the prepared examples and comparative examples are placed in a mold for polymerization reaction, and finally experimental samples of the same shape are obtained. The sample shape used is cylindrical, the diameter of the hydrogel sample is D=10mm, the experimental gauge length is 25 mm, the compression rate of the experimental process is 10mm / min, and the test is carried out at room temperature. During the experiment, the sample is continuously loaded with compressive stress until the sample produces radial micro-cracks and the compression is stopped, and basic data such as the compressive strength of the hydrogel sample can be measured.
[0140] The experimental results are as follows Figure 5 As shown, compared with the three comparative examples, Example 1 has greater compressive strain and compressive strength. It shows that the addition of inorganic nanoparticles can improve the strength of the gel temporary plugging agent system. This is because, on the one hand, the modified nano-inorganic particles are uniformly dispersed in the polymer network of the hydrogel as a reinforcing phase, which can increase the rigidity of the network, thereby improving the compressive strength and toughness of the hydrogel. The nano-inorganic particles effectively transfer loads between polymer chains, inhibit crack propagation, and enhance the material's anti-fracture performance. On the other hand, nano-scale particles have a higher specific surface area and can interact more effectively with polymer chains to form a denser structure, thereby further improving the strength and stability of the overall material.
[0141] 2) Particle mechanical properties
[0142] The mechanical properties of the gel particles are reflected by their storage modulus (G′) and loss modulus (G″), which are tested using a HAAKE rheometer at 25°C. The clamps used are parallel plates with a diameter of 25 mm, and the distance between the clamps is 1000 mm. The strain value is 1% and the frequency is 1 Hz. The particles that have reached swelling equilibrium are added to the sample table for testing, and the sample is pre-controlled at the required temperature before being moved to the sample table. The storage modulus (G′) and loss modulus (G″) of the sample are observed to change with time. Example 1 is a particle temporary plugging agent provided by the present invention, Comparative Example 1 is a conventional PAM-based hydrogel temporary plugging agent for oil fields, Comparative Example 2 is a conventional PAM-based interpenetrating network hydrogel temporary plugging agent for oil fields, and Comparative Example 3 is a nano-composite PAM / MMT hydrogel temporary plugging agent. Before the experiment, the particles were fully swollen at 90°C.
[0143] The experimental results are as follows Figure 6 As shown, the elastic modulus in the embodiment can reach up to 44450Pa, which is much higher than that in comparative example 1. Comparative examples 2 and 3 also improve the elastic modulus to a certain extent. It can be seen that the high elastic modulus is attributed to the synergistic enhancement effect of the interpenetrating network structure and the nanomaterial composite, which is consistent with the design principle of the present invention. The high elastic modulus means that the gel particles can withstand higher stress during the injection or plugging process and have a better application effect.
[0144] (4) Plugging performance test
[0145] In order to clarify the plugging strength of the formed plugging layer, the temporary plugging agent particles were injected into the simulated core with cracks, and the maximum plugging pressure and the time to reach the maximum plugging pressure were used as evaluation indicators. Among them, Example 1 is the particle temporary plugging agent provided by the present invention, and Comparative Example 1 is a conventional PAM-based hydrogel temporary plugging agent in oil fields, 40-70 mesh; Comparative Example 2 is a conventional PAM-based interpenetrating network hydrogel temporary plugging agent in oil fields, 40-70 mesh; Comparative Example 3 is a nano-composite PAM / MMT hydrogel temporary plugging agent, 40-70 mesh; Comparative Example 4: rigid floating bead particles used in block x of xx oil field, 20-40 mesh; Comparative Example 5: weak expansion particle temporary plugging agent used in block x of xx oil field, 30-50 mesh. Before the experiment, the particles were fully swollen at 90°C, and the particle sizes of all samples were uniformly matched with the crack width according to the "one-third" principle, that is, the particle size of the expanded particles after swelling was close to 0.66 mm, the simulated core length was 30 cm, the crack width was 2 mm, the displacement was 50 ml / min, and the temporary plugging agent concentration was 0.5%.
[0146] The experimental results are shown in Table 3. The time to reach the maximum plugging pressure reflects the difficulty of the particles forming a bridge plugging, and the maximum plugging pressure reflects the quality of the temporary plugging performance. The experimental results show that Example 1 has good plugging strength, and it still retains the deformation, adhesion, expansion and other characteristics of the hydrogel particle material, and is more likely to form an effective bridge in the seam.
[0147] Table 3 Plugging performance test results
[0148]
[0149] (5) Degradation performance test
[0150] The bottle test method is used for static evaluation experiments. A certain amount of temporary plugging agent particles and a certain volume of brine are added to a transparent glass tube. The particles are fully swollen at 90°C. After full expansion, the free aqueous solution around the temporary plugging agent particles is removed with a rubber-tipped dropper. The temporary plugging agent without free water is placed in an oven for heating, in order to simulate the oilfield application after the sample particles are injected. In this case, the free solution in which the temporary plugging agent particles were previously dispersed will flow into the surrounding reservoir matrix, while the sample particles that have just expanded will remain in the treatment area. The sample is taken out after a period of time, the remaining sample mass is weighed, and its degradation rate is calculated. The degradation rate can reach 90%, and the degradation rate increases rapidly with increasing temperature, such as Figure 7 As shown. After a certain reaction time, the temporary plugging agent particles gradually self-degrade from transparent water-absorbing and swollen particles to finally become a low-viscosity transparent aqueous solution. The viscosity of the aqueous solution obtained after the swollen sample particles self-degraded in free water for one week was less than 5 mPa⋅s (ambient temperature). The experimental results show that the degradation liquid has low viscosity and very few particles, which meets the requirements of fracturing.
[0151] (6) Degradation fluid core damage test
[0152] Using natural / artificial core columns, the degree of damage to the core permeability of different types of temporary plugging agents after degrading fluid was used was evaluated. Artificial cores with a length of 7 cm and a diameter of 2.5 cm were selected, and the permeability of the initial cores was measured.
[0153] Among them, Example 1 is the particle temporary plugging agent provided by the present invention, Comparative Example 1 is a conventional PAM-based hydrogel temporary plugging agent in oil fields; Comparative Example 2 is a conventional PAM-based interpenetrating network hydrogel temporary plugging agent in oil fields; Comparative Example 3 is a nanocomposite PAM / MMT hydrogel temporary plugging agent.
[0154] The comparative example and the embodiment were respectively brought to a completely degraded state at 90°C, and then the corresponding degradation liquid was injected into the core holder. After the pressure was stable, the inlet and outlet of the holder were closed, and the temperature was maintained at the experimental temperature for 24 hours, and then deionized water was pumped until the pressure was stable. The change in the permeability of the core before and after the injection of the degradation liquid and 24 hours after the injection was calculated, and then the degree of damage to the reservoir by the degradation liquid was evaluated. The pumping displacement was 5mL / min, and the experimental temperature was 90°C. As shown in Table 4, the experimental results show that the degradation liquid will cause certain damage to the permeability of the core after injection. The low-density temporary plugging agent synthesized by inorganic nanoparticles used in the present invention has a small change in permeability before and after flowing through the core. Compared with the commonly used low-density temporary plugging agent synthesized by sodium-based montmorillonite, it is more stable and will not expand or damage the fracturing cracks.
[0155] Table 4 Core permeability changes
[0156]
[0157] Obviously, the embodiments described above are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, ordinary technicians in this field can make other different forms of changes or modifications without creative work, which should fall within the scope of protection of the present invention.
Claims
1. A granular temporary plugging agent, characterized in that: The particle temporary plugging agent has a density lower than that of water and is prepared from the following raw materials, which include the following components in terms of mass percentage: Acrylamide: 17-23%; Comonomer: 1-2%; First cross-linking agent: 0.2-0.27%; Polyvinyl alcohol: 5-10%; Second cross-linking agent: 1-2%; Initiator: 0.06-0.12%; Initiator: 0.01-0.02%; Modified nano-blended materials: 3-6%; Dispersant: 0.3-0.6%; The rest is distilled water; Wherein, the first cross-linking agent is one or more of ethylene glycol dimethacrylate, polyethylene glycol diacrylate, and trimethylolpropane trimethacrylate; The second cross-linking agent is a β-cyclodextrin-boron complex; The modified nano-blended material is a soda lime silicate modified by surface activation-silane coupling, in the form of hollow microspheres filled with air or CO2, with a true density of 0.6 g / cc and a compressive strength of 124 MPa; The comonomer is one or more of 2-acrylamide-2-methylpropanesulfonic acid, p-styrenesulfonic acid, and trimethylolpropane trimethacrylate.
2. The temporary plugging agent according to claim 1, characterized in that: The initiators are two of ammonium persulfate, potassium persulfate and sodium bisulfite, and the mass ratio thereof is 1:
1.
3. The temporary plugging agent according to claim 1, characterized in that: The initiator aid is N,N,N',N'-tetramethylethylenediamine.
4. The temporary plugging agent according to claim 1, characterized in that: The dispersant is one or more of sodium citrate, sodium metasilicate and sodium pyrophosphate.
5. A method for preparing the granular temporary plugging agent according to any one of claims 1 to 4, characterized in that: The steps include: Add polyvinyl alcohol to distilled water, heat at a first temperature and stir until completely dissolved; After the polyvinyl alcohol is completely dissolved to obtain a first solution, the first solution is cooled to room temperature; Add distilled water to acrylamide and the comonomer, and stir thoroughly until they are completely dissolved to obtain a second solution; The first solution is added to the second solution, and the mixture is stirred evenly. During the stirring, a dispersant is added, and after stirring until dissolved, the modified nano-blended material is added, and the mixture is stirred evenly to obtain a first mixture. Adding a first crosslinking agent and an initiator to the first mixture and stirring evenly to obtain a second mixture; Add the second cross-linking agent and the initiator to the second mixture, stir evenly, cover with a plastic wrap, and place in an oven to keep warm at the second temperature for reaction; After the heat preservation reaction is completed, the finished product is taken out to obtain a polymerized jelly colloid, which is dried and crushed to obtain the particle temporary plugging agent; The method further comprises the following steps: adding a second cross-linking agent and an initiating aid to the second mixture, stirring evenly, covering with a preservative film, and placing in an oven for heat preservation reaction at a second temperature, and preparing a second cross-linking agent. The method for preparing the second cross-linking agent comprises: adding β-cyclodextrin to deionized water to obtain a third solution; adding sodium tetraborate to the third solution, and adding sodium hydroxide to adjust the pH value of the solution to between 7 and 8, and continuously stirring at a third temperature until crystals gradually precipitate, wherein the third temperature is 40-80° C.; filtering and collecting the precipitated precipitate, washing the precipitate, and drying to obtain a β-cyclodextrin-boron complex; Before the step of adding the first solution to the second solution, stirring evenly, adding a dispersant during stirring, stirring until dissolved, adding a modified nano-blended material, stirring evenly, and obtaining a first mixture, the preparation method includes preparing a modified nano-blended material, and the step of preparing the modified nano-blended material includes: Place the nano inorganic material in a 2% sodium hydroxide solution and stir evenly; After the reaction is completed, washing and removing the unreacted nano-inorganic material to complete the surface activation of the nano-inorganic material; The activated nano-inorganic material, silane coupling agent, γ-aminopropyltriethoxysilane and ethanol were placed in a three-necked flask, and ammonia water was added and magnetically stirred evenly. Then the temperature was raised to 45°C and stirring was continued for 2 hours. After the stirring was completed, the unreacted raw materials were washed to remove and the modified nano-blend material was obtained by drying.
6. The method for preparing the temporary plugging agent of particles according to claim 5, characterized in that: The first temperature is 90°C-95°C.
7. The method for preparing the temporary plugging agent of particles according to claim 5, characterized in that: The second temperature is 60°C-65°C.
Citation Information
Patent Citations
Degradable fiber blocking agent for drilling fluid and preparation method thereof
CN108384520A
Honeycomb temporary plugging agent for seams and preparation method of honeycomb temporary plugging agent
CN108395883A